Cloning, characterization and mRNA expression of interleukin-6 in blunt snout bream (Megalobrama amblycephala). (July 2016) - Zhang, Chun-Nuan; Zhang, Ji-Liang; Liu, Wen-Bin; Wu, Qiu-Jue; Gao, Xiao-Chan; Ren, Hong-Tao
Abstract: In the present study, the interleukin-6 gene (IL-6) cDNA in blunt snout bream ( Megalobrama amblycephala ) was identified and its expression profiles under ammonia stress and bacterial challenge were investigated. The IL-6 sequence consisted of 1045 bp, including a 696 bp ORF which translated into a 232 amino acid (AA) protein. The protein contained a putative signal peptide of 24 AA in length. IL-6 expression analysis showed that the it is differentially expressed in various tissues under normal conditions and the highest IL-6 level was observed in the intestine tissue, followed by the liver, and then in the gills. Under ammonia stress, the IL-6 mRNA level both in spleens and intestine increased significantly ( P < 0.05), with the maximum levels attained at 6 h, 12 h (72, 10-fold, respectively). Thereafter, they all significantly decreased ( P < 0.01) and returned to the basal value within 48 h. Whereas, in livers it slightly decreased at 3 h firstly (0.5-fold), and then significantly ( P < 0.05) increased with the maximum level attained 12 h (3-fold). Further expression analysis showed that the mRNA level of IL-6 in spleens, intestine and livers of blunt snout bream all increased significantly ( P < 0.05), with maximum values attained at 6 h, 3 h, 6 h (10, 6, 18-fold, respectively) after Aeromonas hydrophila ( A. hydrophila ) injection, and then decreased to the basal value within 24 h which suggested that IL-6 was involved in the immune response to A. hydrophila. The cloning and expression analysis of the IL-6 provide theoretical basis to further study the mechanism of anti-adverseness and expression characteristics under stress conditions in blunt snout bream. Highlights: The IL-6 gene in Megalobrama amblycephala was characterized. IL-6 gene was highly expressed in immune-relevant tissues. IL-6 levels firstly increased and then decreased following ammonia stress. IL-6 was involved in response to Aeromonas hydrophila challenge.